Quick and reliable method to analyze meiotic segregation patterns in Coprinus cinereus using the polymerase chain reaction - T. Freedman; P. J. Pukkila (Fungal Genetics Reports, 1993)
It is well known that multiple auxotrophic markers impede fruiting in Coprinus cinereus. Restriction fragment length polymorphisms have been used to advantage (Cassidy et al. 1984 Curr. Genet. 8:607-613; Zolan et al. 1992 Nucl. Acids Res. 20:3993-3999) but the required Southern analysis is both time consuming and laborious.